THE EFFECT OF CIGARETTE EXCISE INCREASE AND CONSUMPTION BEHAVIOR ON THE PREVALENCE OF SMOKERS IN INDONESIA: THE ROLE OF HOUSEHOLD EXPENDITURE AS AN INTERVENING - Alkaromi, Muhammad Amri (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study examines the effect of cigarette excise increase and consumption behavior on the prevalence of smokers in Indonesia, with household expenditure as an intervening variable. Indonesia has one of the highest prevalence rates of smokers in the world, which has a significant impact on public health and household economic conditions. Method: Using a quantitative approach and survey-based data collection, the number of samples was determined through the stratified random sampling method with the number of samples obtained as many as 100 respondents with smokers over the age of 17 years in East Java Province. Results: The results of the study show that the increase in cigarette excise does not directly affect household spending on cigarettes. Cigarette consumption behavior is the main factor that determines the amount of household spending. Household expenditure plays an intervening variable that links the increase in cigarette excise with the prevalence of smokers. The increase in cigarette excise has a direct impact on the prevalence of smokers, but the impact is partly mediated by household spending. Novelty: To support the Government's steps in increasing cigarette excise, it should be accompanied by additional policies, such as health campaigns and restrictions on access to cigarettes. As well as additional regulations such as the ban on cigarette advertising and the smoker rehabilitation program can strengthen the effect of the excise increase.